Exploration of The Potential of Suwangi Tourism Village Through Swot Analysis in East Lombok Regency, Indonesia - Junaidi, Muhammad Adi; Rochmi, Evilia; Ramli, Muhammad; Mawalina, Mawalina; Firmansyah, Kukuh; Sari, Mira (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
Suwangi Village is one of the villages located in Sakra District, East Lombok Regency. Suwangi Village is trying to pioneer a tourism village through natural, cultural, artificial, and special interest tourism. Therefore, to develop the potential of Suwangi village, a strategy is needed to make a tourism village that can continue to grow and attract the attention of tourists to visit. This research uses qualitative descriptive methods and uses Strenght, Weakness, Opportunity and Threat Analysis so that the strengths and weaknesses of the village can be recognized and to see the opportunities and threats faced to pioneer Suwangi Village into a tourist village. Based on the results obtained, several aspects that become the strength of Suwangi village's tourist attraction include natural beauty that is still natural, a fairly large area, has relics that are considered sacred and preserved until now. In addition, public awareness and understanding of the management and development of tourist destinations is still limited, becoming a weakness of the management of this tourist village. It can also be known opportunities and threats such as natural disasters, public perceptions that have not been educated about tourism tend to think negatively to be an obstacle to tourism development, and security is still not good. Although it still has some shortcomings, the potential tourist attraction of Suwangi village is quite adequate as a competitive tourist village.